Spatially explicit estimates of prey consumption reveal a new krill predator in the Southern Ocean. - Andrea Walters; Mary-Anne Lea; John van den Hoff; Iain C Field; Patti Virtue; Sergei Sokolov; Matt H Pinkerton; Mark A Hindell (PLoS ONE, 2014)
Development in foraging behaviour and dietary intake of many vertebrates are age-structured. Differences in feeding ecology may correlate with ontogenetic shifts in dispersal patterns, and therefore affect foraging habitat and resource utilization. Such life-history traits have important implications in interpreting tropho-dynamic linkages. Stable isotope ratios in the whiskers of sub-yearling southern elephant seals (Mirounga leonina; n = 12) were used, in conjunction with satellite telemetry and environmental data, to examine their foraging habitat and diet during their first foraging migration. The trophic position of seals from Macquarie Island (54°30'S, 158°57'E) was estimated using stable carbon (δ(1) (3)C) and nitrogen (δ(15)N) ratios along the length of the whisker, which provided a temporal record of prey intake. Satellite-relayed data loggers provided details on seal movement patterns, which were related to isotopic concentrations along the whisker. Animals fed in waters south of the Polar Front (>60°S) or within Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) Statistical Subareas 88.1 and 88.2, as indicated by both their depleted δ(1) (3)C (<-20‰) values, and tracking data. They predominantly exploited varying proportions of mesopelagic fish and squid, and crustaceans, such as euphausiids, which have not been reported as a prey item for this species. Comparison of isotopic data between sub-yearlings, and 1, 2 and 3 yr olds indicated that sub-yearlings, limited by their size, dive capabilities and prey capture skills to feeding higher in the water column, fed at a lower trophic level than older seals. This is consistent with the consumption of euphausiids and most probably, Antarctic krill (Euphausia superba), which constitute an abundant, easily accessible source of prey in water masses used by this age class of seals. Isotopic assessment and concurrent tracking of seals are successfully used here to identify ontogenetic shifts in broad-scale foraging habitat use and diet preferences in a highly migratory predator.